MITIGATION CLIMATE DISASTER BASED ON QS YUSUF 47-49 - Endin Mujahidin; Bahagia .; Ahmad Mulyadi Kosim; Fachrudin Majeri Mangunjaya (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
The objective of this research is to discover about mitigation climate disaster in QS Yusuf 47-49. The method used is a literature review or library research without collecting data in the field with a descriptive approach. The data research is gathered through reading, collecting, and processing data based on numerous sources comprises a book, journal, article, and hadit as well as Qs-Al-Quran. The result shows that Yusuf prophet releases climate adaptation through surmising climate such as drying and the rainy season before the season combat the society. It refers to avoid human from some adverse effect of climate. Society in Yusuf prophet era providing staple food for facing drying season. As result as a society avoid the shortage of fundamental need when they experience extreme weather. The other is Yusuf prophet forecast weather both drying and rainy period to prefer human for another further mitigation. The other is Yusuf prophet reminds the society through building disaster communication before disaster strike society, it can be categorized as non-physic mitigation of disaster where communication makes them literate about ecology disaster before eco-catastrophe harm human. The impact is to salvage community from the possible side effect of disaster. Lastly, society in Yusuf prophet has conducted physical mitigation like building storage for food because it impossible as food doesn't save in house or food storage.